PENGKONDISIAN KESIAPAN BELAJAR UNTUK PENCAPAIAN HASIL BELAJAR DENGAN GERAKAN SENAM OTAK - Susanto, Ratnawati (Eduscience : Jurnal Ilmu Pendidikan, 2018)
AbstractEducation often places emphasis on learning outcomes as a problem. The reality of learning outcomes is the impact of how learners have readiness to learn. Research mixed methods with one-pretest-Postest experimental design aims to address the problem of how conditioning the readiness of learning needs to be done by educators to achieve learning outcomes as behavioral changes that include knowledge, attitudes and skills that can be observed and measured. The result of the research with sample of 30 FKIP UEU students with Slovin technique proves that: (1) The process of applying of brain gymnastics can be integrated as initial activity, core and end of learning, and there is strong and highly significant positive influence between (2) conditioning of learning readiness without gymnastics brain with learning readiness, (2) conditioning without brain gymnastics learning readiness (r = 0.783, R2 = 61.4%); (3) conditioning without brain exercise on learning outcomes (r = 0.688, R2 = 47.3%); (4) Conditioning learning with brain exercises against learning readiness (r = 0.799, R2 = 63.9%); (5) Conditioning learning with brain exercises on learning outcomes (r = 0.693, R2 = 48.1%); and there is a strong, positive and significant difference between pre and post brain gymnastics learning at (6) learning readiness (mean = 2.94, r = 0.784, and (7) learning outcomes (mean = 9.74, r = 0.765 ). Keywords: conditioning learning readiness, learning outcomes, brain gym AbstrakDunia pendidikan seringkali memberi penekanan terhadap hasil belajar sebagai suatu masalah. Kenyataannya hasil belajar adalah dampak dari bagaimana peserta didik memiliki kesiapan belajar. Penelitian mixed methods dengan desain eksperimen one group pretest–Postest bertujuan untuk menjawab permasalahan mengenai bagaimana pengkondisian kesiapan belajar perlu dilakukan pendidik untuk pencapaian hasil belajar sebagai perubahan tingkah laku yang mencakup pengetahuan, sikap dan keterampilan yang dapat diamati dan diukur. Hasil penelitian dengan sampel 30 mahasiswa FKIP UEU dengan teknik Slovin membuktikan bahwa: (1) Proses penerapan senam otak dapat diintegrasikan sebagai kegiatan awal, inti dan akhir pembelajaran, dan terdapat pengaruh yang positif kuat dan sangat signifikan antara (2) pengkondisian kesiapan belajar tanpa senam otak dengan kesiapan belajar, (2) Pengkondisian belajar tanpa senam otak terhadap kesiapan belajar (r = 0,783, R2 = 61,4%); (3) Pengkondisian belajar tanpa senam otak terhadap hasil belajar (r = 0,688, R2 = 47,3%) ; (4) Pengkondisian belajar dengan senam otak terhadap kesiapan belajar (r = 0,799, R2 = 63,9% ); (5) Pengkondisian belajar dengan senam otak terhadap hasil belajar (r = 0,693, R2= 48,1%); dan terdapat perbedaan yang kuat, positif dan signifikan Pengkondisian belajar sebelum dan setelah senam otak pada: (6) Kesiapan belajar (mean = 2,94, r = 0,784 ; dan (7) Hasil belajar (mean = 9,74, r = 0,765). Kata kunci: pengkondisian kesiapan belajar, hasil belajar, senam otak